Rationale for and design of the Idiopathic Pulmonary Fibrosis–PRospective Outcomes (IPF-PRO) registry. Issue 1 (11th January 2016) - O'Brien, Emily C; Durheim, Michael T; Gamerman, Victoria; Garfinkel, Sandy; Anstrom, Kevin J; Palmer, Scott M; Conoscenti, Craig S
Abstract : Background: Idiopathic pulmonary fibrosis (IPF) is a chronic interstitial lung disease characterised by progressive loss of lung function. Its clinical course is variable but ultimately fatal. There is a need for a multicentre patient registry incorporating longitudinal clinical data and biological samples to improve understanding of the natural history of IPF and contemporary practice patterns. Methods/design: The Idiopathic Pulmonary Fibrosis–PRospective Outcomes (IPF-PRO) registry is a national IPF registry in the USA. This registry will enrol approximately 300 patients with newly diagnosed IPF over 2 years at approximately 14 tertiary pulmonary care sites. Participants will be followed for 3–5 years and will receive usual care, as defined by their physician. Clinical data from the year prior to diagnosis will be collected from medical record review on enrolment. Subsequently, data on diagnostic evaluations, pulmonary function tests, physical examinations, laboratory data and clinical events will be collected at routine clinical visits and via a call centre. Participants will complete patient-reported outcome questionnaires at enrolment and then at approximately 6-month intervals. Blood samples for cellular, genetic and transcriptomic analyses will be collected at the same intervals. Results: The first results from the IPF-PRO registry will be presented in 2015. Conclusions: The IPF-PRO registry will improve understanding of the natural history of IPF, its impact on patients and current practice in the diagnosis and care of patients with IPF. The registry will establish a repository of biological samples from a well-characterised patient population for future research. Clinical trial number: NCT01915511.